General invariant forms of the anisotropic failure criteria - Thinh, Tran Ich (Vietnam Journal of Mechanics, 1993)
The general invariant forms of failure criteria for anisotropic solids were studied and applied to orthotropic composite materials. when subjected to three-dimensional stress states with rotational symmetry. The Hill criterion and the Tsai and Wu criterion are special cases of these general forms.